Textile Structural Composites - Ko Frank K; Ayranci Cagri; Pastore Christopher M (DEStech Publications, 2023)
The broad range of applications for textile structural composites can be attributed to the unique combination of formability, damage tolerance, and affordability of TSCs. This text provides a technical introduction to the design, manufacture, and testing of textile reinforced composite materials for structural applications and beyond. The prose is written in an accessible, straightforward, and practical way suitable for instructional use. Written by experts in both textiles and composite materials science, the book covers the formation of near-net-shape composites from 2-D and 3-D textiles made from natural and synthetic fibers, including carbon and glass. There is a special stress on preforms produced with textile operations such as weaving, knitting and braiding. This is followed by a description of how textile composites are made with polymer, metal, and ceramic matrices. Design calculations are provided, starting with micromechanical features and moving toward finished components. The experiments and tests unique to textile composites are outlined and differentiated from tests for monolithic and laminated materials.